Comparison of Outcomes between Robot‐Assisted Minimally Invasive Transforaminal Lumbar Interbody Fusion and Oblique Lumbar Interbody Fusion in Single‐Level Lumbar Spondylolisthesis. Issue 7 (1st October 2021) - Han, Xiao‐guang; Tang, Guo‐qing; Han, Xiao; Xing, Yong‐gang; Zhang, Qi; He, Da; Tian, Wei
Abstract : Objective: To compare the safety and effectiveness of robot‐assisted minimally invasive transforaminal lumbar interbody fusion (Mis‐TLIF) and oblique lumbar interbody fusion (OLIF) for the treatment of single‐level lumbar degenerative spondylolisthesis (LDS). Methods: This is a retrospective study. Between April 2018 and April 2020, a total of 61 patients with single‐level lumbar degenerative spondylolisthesis and treated with robot‐assisted OLIF (28 cases, 16 females, 12 males, mean age 50.4 years) or robot‐assisted Mis‐TLIF (33 cases, 18 females, 15 males, mean age 53.6 years) were enrolled and evaluated. All the pedicle screws were implanted percutaneously assisted by the TiRobot system. Surgical data included the operation time, blood loss, and length of postoperative hospital stay. The clinical and functional outcomes included Oswestry Disability Index (ODI), Visual Analog scores (VAS) for back and leg pain, complication, and patient's satisfaction. Radiographic outcomes include pedicle screw accuracy, fusion status, and disc height. These data were collected before surgery, at 1 week, 3 months, 6 months, and 12 months postoperatively. Results: There were no significantly different results in preoperative measurement between the two groups. There was significantly less blood loss (142.4 ± 89.4 vs 291.5 ± 72.3 mL, P < 0.01), shorter hospital stays (3.2 ± 1.8 vs 4.2 ± 2.5 days, P < 0.01), and longer operative time (164.9 ± 56.0 vs 121.5 ± 48.2 min, P < 0.01) in OLIF group compared with Mis‐TLIF group. The postoperative VAS scores and ODI scores in both groups were significantly improved compared with preoperative data ( P < 0.05). VAS scores for back pain were significantly lower in OLIF group than Mis‐TLIF group at 1 week (2.8 ± 1.2 vs 3.5 ± 1.6, P < 0.05) and 3 months postoperatively (1.6 ± 1.0 vs 2.1 ± 1.1, P < 0.05), but there was no significant difference at further follow‐ups. ODI score was also significantly lower in OLIF group than Mis‐TLIF group at 3 months postoperatively (22.3 ± 10.0 vs 26.1 ± 12.8, P < 0.05). There was no significant difference in the proportion of clinically acceptable screws between the two groups (97.3% vs 96.2%, P = 0.90). At 1 year, the OLIF group had a higher interbody fusion rate compared with Mis‐TLIF group (96.0% vs 87%, P < 0.01). Disc height was significantly higher in the OLIF group than Mis‐TLIF group (12.4 ± 3.2 vs 11.2 ± 1.3 mm, P < 0.01). Satisfaction rates at 1 year exceeded 90% in both groups and there was no significant difference (92.6% for OLIF vs 91.2% for Mis‐TLIF, P = 0.263). Conclusion: Robot‐assisted OLIF and Mis‐TLIF both have similar good clinical outcomes, but OLIF has the additional benefits of less blood loss, less postoperative hospital stays, higher disc height, and higher fusion rates. Robots are an effective tool for minimally invasive spine surgery. Abstract : Robot‐assisted OLIF and Mis‐TLIF both have similar good clinical outcomes, but OLIF has the additional benefits of less blood loss, less hospital stays, higher disc height, and higher fusion rates. Robots can improve the safety of the minimally invasive spine surgery.